2020
DOI: 10.3390/jof6030163
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Echinocandin-Resistant Candida glabrata Bloodstream Infection Complicating COVID-19: A Fatal Case Report

Abstract: Coinfections with bacteria or fungi may be a frequent complication of COVID-19, but coinfections with Candida species in COVID-19 patients remain rare. We report the 53-day clinical course of a complicated type-2 diabetes patient diagnosed with COVID-19, who developed bloodstream infections initially due to methicillin-resistant Staphylococcus aureus, secondly due to multidrug-resistant Gram-negative bacteria, and lastly due to a possibly fatal Candida glabrata. The development of FKS-associated pan-echinocand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 52 publications
2
92
0
1
Order By: Relevance
“…The overall incidence varied from 0.7% to 23.5%, and the majority of patients with candidemia were in an ICU and had been exposed to various factors associated with candidemia, including central venous catheter, broad‐spectrum antibiotics, corticosteroids and parenteral nutrition. Remarkably, surgery was reported in only one case (vascular surgery, which is not a classical predisposing factor for candidemia) 19 …”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence varied from 0.7% to 23.5%, and the majority of patients with candidemia were in an ICU and had been exposed to various factors associated with candidemia, including central venous catheter, broad‐spectrum antibiotics, corticosteroids and parenteral nutrition. Remarkably, surgery was reported in only one case (vascular surgery, which is not a classical predisposing factor for candidemia) 19 …”
Section: Discussionmentioning
confidence: 99%
“… A. The total number of severely ill patients was not determined for studies from Italy [ 24 ], Greece [ 21 ], and Oman [ 25 ]. AKD: Acute kidney disease; CKD: Chronic kidney disease; CLD: Chronic liver disease; COPD: Chronic obstructive pulmonary disease; DM: Diabetes mellitus; HT: Hypertension; IHD: Ischemic heart diseases; CVC: Central venous catheter; UC: Urinary catheter; AMB: Amphotericin B; LAMB: Liposomal AMB; MFG: Micafungin; CAS: Caspofungin; VRC: Voriconazole; FLC: Fluconazole; S: Susceptible; FLCR: Fluconazole-resistant; AMBR: Amphotericin B-resistant; IFR: Intrinsically fluconazole-resistant MAR: Multiazole-resistant; MDR: Multidrug-resistant; PER: Pan-echinocandin-resistant; ND: Not determined; PCR: Polymerase chain reaction; BDG: Beta-d-glucan.…”
Section: Tablementioning
confidence: 99%
“…Despite the recognition that airborne Aspergillus fumigatus is increasingly recognized as an important cause of fungal super-infections among critically ill COVID-19 patients [ 19 ], the incidence of candidiasis has not been evaluated in this context. Indeed, the wide use of antibiotics, corticosteroids, and central venous catheters, along with the damage exerted by SARS CoV-2 among patients with ARDS [ 19 ], may allow commensal Candida to cells to invade internal organs [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. The goals of this manuscript are to review our current knowledge on Candida super-infections among COVID-19 patients, discuss the potential immunological and clinical factors predisposing these patients to invasive candidiasis, and outline what studies are needed to better define the epidemiology of this superinfection.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies-from, in particular, Germany, Italy and the US-have reported outbreaks or an increase in infections with and/or acquisition of multidrug-resistant bacteria during the COVID-19 pandemic [9][10][11][12]. Further studies have reported cases of antimicrobial-resistant invasive fungal infections in COVID-19 patients [13,14], and one case of azole-resistant Aspergillus spp. infection in an immunocompetent COVID-19 patient [15].…”
mentioning
confidence: 99%